KERJASAMA ILO – RI DALAM MEMPROMOSIKAN HAK KESEMPATAN KERJA YANG ADIL BAGI PENYANDANG DISABILITAS DI INDONESIA - Yulianti Rajagukguk; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study is a contemporary study that provides an analysis of ILO - RI cooperation in promoting the right of fair work opportunity for disabled persons in indonesia. This study aims to explain the inequality that occurs in the right of employment for disabled persons in indonesia. In developing countries like Indonesia, disabled persons are often overlooked, so that many of disabled persons do not have the right to work. ILO as an international organization that focusing on workers' rights is concerned to help promote the rights of disabled persons in indonesia.This research was developed based on the framework of pluralism perspective that is supported by the theory of international organization, as well as the level of analysis using society as the main actor in international relations. The concept leads to qualitative methods and the study of literature as a source of information.ILO-Indonesia cooperation are in promoting the PROPEL-Indonesia program. The program supports governments, as well as other key stakeholders in improving awareness and awareness on the rights of disabled persons, especially in work and training terms in partnership with partners.Keywords: Disabled Persons, Cooperation, Inequality, ILO, Indonesia